THE EFFECT OF FOREIGN EXCHANGE RESERVES, INFLATION, AND MONEY SUPPLY ON THE EXCHANGE RATE IN INDONESIA - A. Mahendra; Witya Shalini; Amelia Novizar (RADJA PUBLIKA, 2025)
This research aims to determine the influence of foreign exchange reserves, inflation, and the money supply on the exchange rate in Indonesia. The population in this study is Indonesia, and 25 of them were selected as samples through a purposive sampling technique. Estimates were conducted using multiple regression analysis. The data used in this study were secondary data, consisting of foreign exchange reserves, inflation, and the money supply on the exchange rate for the years 2000-2024. The results of this research show that, based on the partial t-test, foreign exchange reserves and the money supply have a significant effect on the exchange rate in Indonesia, but inflation does not. The simultaneous t-test (F-test) showed that foreign exchange reserves, inflation, and the money supply have a significant effect on the exchange rate.